Government Spending And Economic Growth Nexus In Sub-Saharan Africa: An Econometric Analysis - Mathew Owusu-Mensah; Christiana Afriyie Manu; Peter Arhenful (European Scientific Journal, ESJ, 2023)
Proponents of larger governments argue that government programmes provide essential public goods like education and infrastructure, which, in turn, stimulate the economy. On the other hand, individuals who advocate for more limited government assert that an increase in public spending will be detrimental to economic expansion due to the fact that many functions of government are inefficient and not in the public interest. Secondary data from World development indicator variables spanning from 1985 to 2021 were analysed. The dependent variable for the study was GDP per capita and the independent variables were institutional quality, government expenditure, capital stock and trade openness. The model used for the study are Pearson correlation, Pesaran's , Friedman's and Frees' cross sectional dependency test, IPS and CIPS unit root test, Pooled Mean Group and Dynamic Fixed Effect regression to test for the long-run cointegration and short-run relationship in 32 African countries. The results of the study suggest that there exists a long-run and short-run relationship between government expenditure and economic growth. Additionally, the study emphasises the importance of institutional quality as a significant determinant of this relationship. Therefore, it is recommended that all accessible government funds be allocated towards the objective of establishing durable and self-sufficient infrastructure.